2008
DOI: 10.1590/s0101-20612008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Produção de biscoitos extrusados de polvilho azedo com fibras: efeito de parâmetros operacionais sobre as propriedades físicas

Abstract: A mandioca é uma cultura plantada em mais de 90 países, alimentando cerca de 500 milhões de pessoas em todo o mundo. A produção da raiz continua crescendo na maioria dos países que a cultivam, passando de 97 milhões de toneladas para 203 milhões de toneladas em 30 anos. A produção brasileira de mandioca está em torno de 26,5 milhões de toneladas por ano, sendo esta cultura plantada em 87% dos municípios brasileiros (IBGE, 2006). Na agroindustrialização da mandioca, um produto de importância e tradição é o polv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
4
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 4 publications
0
11
4
14
Order By: Relevance
“…The results were higher than the ones reported by CAMARGO et al (2008), who assessed extruded biscuits from sour starch and fiber and observed variation from 23.17 to 29.23%. Solubility showed a positive linear effect of temperature and negative linear and positive quadratic effect of moisture.…”
Section: Resultscontrasting
confidence: 85%
“…The results were higher than the ones reported by CAMARGO et al (2008), who assessed extruded biscuits from sour starch and fiber and observed variation from 23.17 to 29.23%. Solubility showed a positive linear effect of temperature and negative linear and positive quadratic effect of moisture.…”
Section: Resultscontrasting
confidence: 85%
“…The graph area with higher EI values (above 3.0) has a semi-elliptical shape and is thus the product becomes denser and the bubble growth is compressed, as observed in the present study. Camargo, Leonel and Mischan (2008) studied the effect of moisture and extrusion temperature on the specific volume of snacks of cassava starch and soy flour, and reported values between 1.5 to 5.6 mL.g -1 , which are lower than those found in the present study.…”
Section: Resultscontrasting
confidence: 84%
“…The crude fiber was determined by the Scharrer-Kürschner method, as described by Angelucci et al (1987), using nitric acid, trichloroacetic acid, and acetic acid for hydrolysis. The total energy was estimated using the Atwater conversion factors; the content of carbohydrate (minus the crude fiber content) and protein were multiplied by four; lipid content was multiplied by nine, and the sum of the products' content resulted in the value of total energy (BRASIL, 2003). The chemical composition data of the snacks evaluated were compared with those of the corn snacks reported by Bombo (2006).…”
mentioning
confidence: 99%
“…To calculate the density, an analytical balance was used to determine the mass, and the volume was determined by the millet-seed displacement method using a graduated cylinder (CAMARGO; LEONEL; MISCHAN, 2008). Water activity of the cereal bars was measured using a water activity meter (AquaLab model CX-2, Decagon Devices Inc., Pullman, WA) under controlled temperature.…”
Section: Physical Characteristicsmentioning
confidence: 99%